BILINGUAL EDUCATION IN FORMER SOVIET COUNTRY: PERSPECTIVE AND PROBLEMS - Vasic Bibigul; Bibigul Kussanova Khakimovna; Summers Danna; Maydangalieva Zhumagul Aldiyarovna (Scientific Journal of Pedagogy and Economics, 2019)
This article describes the sociocultural phenomenon development of bilingualism in Kazakhstan. The language pluralism in Kazakhstan is considered as a result of the past social and political and economic reforms. Kazakhstan society is more open today compare with Soviet time. The globalization promotes that foreign languages are necessary for nations. Foreign language skills expand the professional competence of the expert, open access to the world, and make the expert competitive not only in national but also on a global scale. According to Nazarbayev, the relevance of polylingual education is "one of the important values and the main advantage of our country." The program of bilingual training provides the creation of the new model of education. The fluency in Kazakh, English and Russian languages will help youth adjusting to world labor markets, science, and new technologies will create conditions for social attitudes which based on the collaboration of Kazakh, Russian and Western cultures. Currently, modern economic space distinguishes the importance of multilingualism. The article reflects the authors’ opinion within the social research in secondary school Aktobe city, Aktobe region.